Navigating Blackness in the African Diaspora - Yates, Sarah (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2020)
This thesis offers a comparative reading of Ralph Ellison's Invisible Man, Percival Everett's Erasure, Zoë Wicomb's Playing in the Light and NoViolet Bulawayo's We Need New Names in order to explore the diversity of subjectivities included within the terms 'African' and 'black' and to argue for the necessity of renewed definitions of Africa(nness) and blackness which allow for diverse and fluid representations. The diverse historical and political contexts in which these novels are published, as well as the critical and theoretical discussions which surround them demonstrate an evolution in literary portrayals of identity politics. As the categories of race and nation become more fluid, so too do narrative forms. In particular, this thesis is interested in the textual strategies authors use to navigate the various ways in which depictions of blackness continue to be restricted by racism, stereotypes, and the dynamics of a global literary market. As portrayals and discussions of identity politics proliferate in popular culture, they become increasingly commodified, and therefore increasingly restricted by the market.
Keywords: Ellison, Ralph. Invisible man; Everett, Percival. Erasure; Wicomb, Zoe. Playing in the light; Bulawayo, NoViolet. We need new names; Africans in literature; Race in literature; African fiction (English) -- History and criticism